Pengaruh Kepemilikan Manajerial Dan Ukuran Perusahaan Terhadap Kinerja Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2020-2024 - Fitrianti .; Elfiswandi .; Putri Intan Permata sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine the effect of managerial ownership and company size on company performance, with capital structure as an intervening variable, listed in the food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange. The population in this study consisted of 99 food and beverage sub-sector manufacturing companies. The sample in this study was taken using a purposive sampling method, obtaining a sample of 16 companies. The data analysis method in this study used descriptive statistical analysis, classical assumption tests, multiple linear regression tests, hypothesis tests, and path analysis. The results of the study indicate that managerial ownership and company size have a significant influence on capital structure. In addition, company size and capital structure have a significant influence on company performance. However, managerial ownership has an insignificant effect on company performance. Furthermore, the results of the analysis show that capital structure is unable to mediate the effect of managerial ownership on company performance, and is unable to mediate the effect of company size on company performance. This indicates that managerial ownership and company size influence company performance more directly than through capital structure mechanisms. It is hoped that food and beverage sub-sector manufacturing companies can improve the related variables in the study so that they can achieve their stated company goals.